Battered Woman Syndrome: Prospect of Situating It Within Criminal Law in India - A. Deb (BRICS Law Journal, 2021)
In patriarchal cultures, like the one prevalent in India, rigid, polarised and hierarchical gender roles work to establish a strong normative relationship between gender and the treatment of offenders committing violent crimes such as homicide. While most of the common law countries have already undergone a social change towards making their criminal laws more gender-sensitive by accommodating the experiences of battered women, the situation in India is quite different. Indian courts have recognised Battered Woman Syndrome very recently in only three cases, much differently than courts in other jurisdictions. While in other countries, Battered Woman Syndrome has been adduced by the advocates of battered women to support defence pleas, Indian Courts have resorted to it only to explain the effects of a battering relationship. The fact that Battered Woman Syndrome has only been recognised in such a small number of cases and the lack of scholarship in this particular area clearly resonates the resistance of the Indian criminal law towards women’s accounts of their experiences. Drawing on the example of the three cases, the author makes an attempt to put forth feminist legal arguments and offer a fresh perspective on the possibility of using Battered Woman Syndrome as a defence to address the concerns of battered women who end the cycle of violence by ending the lives of the abuser in a “kill or be killed” situation. Since Battered Woman Syndrome as a subject has been extensively researched in other common law countries, the present study limits itself to the Indian jurisdiction only. This paper also challenges the effectiveness of the existing defences under the Indian Penal Code, 1860 in accommodating the cases of battered women, and highlights the need for the introduction of a new justificatory defence as a plausible solution.